2022
DOI: 10.1039/d2nj03696g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of hydrophilic Ag2Se quantum dots optically optimized by multivariate strategies: an easy one-pot approach

Abstract: A simple and fast aqueous synthesis of silver selenide quantum dots is proposed with the aid of multivariate optimization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…34 Similar results were also reported in the literature, with orthorhombic being a typical crystalline phase for Ag 2 Se. 10,21,24,35 Images obtained by transmission electron microscopy (Fig. 8) confirmed that the Ag 2 Se nanoparticles showed a spherical shape with a mean diameter of 6.0 AE 3.4 nm.…”
Section: Structural and Morphological Characterization Of Ag 2 Se-mpa...mentioning
confidence: 65%
See 4 more Smart Citations
“…34 Similar results were also reported in the literature, with orthorhombic being a typical crystalline phase for Ag 2 Se. 10,21,24,35 Images obtained by transmission electron microscopy (Fig. 8) confirmed that the Ag 2 Se nanoparticles showed a spherical shape with a mean diameter of 6.0 AE 3.4 nm.…”
Section: Structural and Morphological Characterization Of Ag 2 Se-mpa...mentioning
confidence: 65%
“…This broad absorption profile is typical of Ag 2 Se QDs and has been reported in the literature. 10,21 In general, for most samples that differ only by reaction time, the longer time (180 min) resulted in higher PL intensities, with little change in the absorption and PL emission profiles. Besides, for all the samples a wavelength emission higher than 900 nm was observed, similar to other works that report the preparation of Ag 2 Se-MPA.…”
Section: Results From the 2 4à1 Fractional Factorial Experimental Des...mentioning
confidence: 93%
See 3 more Smart Citations